ANTIBIOTIC RESIDUAL TEST IN LUNGS OF BALI COWS FROM SOME MARKETS IN BALI PROVINCE - Pane, Maria Elysabet; Samsuri, Samsuri; Sudira, I Wayan (Buletin Veteriner Udayana, 2020)
The use of antibiotics in inappropriate cattle ranches, for example, excessive doses, and no regard for drug withdrawal can cause antibiotic residues in the flesh and also the organs in livestock. The withdrawal time is the period from the last drug delivery to the livestock before the animal can be slaughtered so the meat and internal organs can be consumed. The lung is one of the internal organs distributed antibiotics that when not pay attention to the time of stopping the drug at the time of cutting the lung organ will still contain active substances from these antibiotics that cause the presence of antibiotic residues. This study aims to determine the presence of antibiotic residues in the lungs of bali cattle from several markets in Bali province. 30 lung samples were taken from several markets in five districts of Tabanan, Gianyar, Buleleng, Jembrana, and Karangasem and then tested using the bioassay method at Balai Besar Veteriner Denpasar. The results showed that 30 lung samples did not contain antibiotic residues of the penicillin, aminoglycoside, tetracycline, and macrolide groups.